Potential therapeutic effects of traditional Chinese medicine in acute mountain sickness: pathogenesis, mechanisms and future directions - Wu, Zhenhui; Wang, Yihao; Gao, Rong; Chen, Junru; Chen, Yingfan; Li, Maoxing; Gao, Yue (Frontiers in Pharmacology, 2024)
Backgr ound and objectives: Acute mountain sickness (AMS) is a pathology with different symptoms in which the organism is not adapted to the environment that occurs under the special environment of high altitude. Its main mechanism is the organism's tissue damage caused by acute hypobaric hypoxia. Traditional Chinese medicine (TCM) theory focuses on the holistic concept. TCM has made remarkable achievements in the treatment of many mountain sicknesses. This review outlines the pathogenesis of AMS in modern and traditional medicine, the progress of animal models of AMS, and summarizes the therapeutic effects of TCM on AMS. Methods: Using the keywords "traditional Chinese medicine", "herbal medicine", "acute mountain sickness", "high-altitude pulmonary edema", "high-altitude cerebral edema", "acute hypobaric hypoxia", and "high-altitude", all relevant TCM literature published up to November 2023 were collected from Scopus, Web of Science, PubMed, and China National Knowledge Infrastructure databases, and the key information was analyzed. Results: We systematically summarised the effects of acute hypobaric hypoxia on the tissues of the organism, the study of the methodology for the establishment of an animal model of AMS, and retrieved 18 proprietary Chinese medicines for the clinical treatment of AMS. The therapeutic principle of medicines is mainly invigorating qi, activating blood and removing stasis. The components of botanical drugs mainly include salidroside, ginsenoside Rg1, and tetrahydrocurcumin. The mechanism of action of TCM in the treatment of AMS is mainly through the regulation of HIF-1α/NF-κB signaling pathway, inhibition of inflammatory response and oxidative stress, and enhancement of energy metabolism. Conclusion: The main pathogenesis of AMS is unclear. Still, TCM formulas and components have been used to treat AMS through multifaceted interventions, such as compound danshen drip pills, Huangqi Baihe granules, salidroside, and ginsenoside Rg1. These components generally exert anti-AMS pharmacological effects by inhibiting the expression of VEGF, concentration of MDA and pro-inflammatory factors, down-regulating NF-κB/NLRP3 pathway, and promoting SOD and Na+ -K+ -ATPase activities, which attenuates acute hypobaric hypoxia-induced tissue injury. This review comprehensively analyses the application of TCM in AMS and makes suggestions for more in-depth studies in the future, aiming to provide some ideas and insights for subsequent studies.